Intangible assets and investments at the sector level: Empirical evidence for Germany - Dirk Crass; Georg Licht; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper investigates the role intangible capital plays for economic growth in different sectors in Germany. It consists of two major parts. In the first part, we aim at measuring investment in intangibles at the sector level. We shed light on differences across sectors but also compare these figures with investment in physical capital and with investment in intangibles in the UK as European benchmark. The second part explores the role of intangible assets for stimulating growth at the sector level by performing growth accounting analyses. We find that German firms have boosted investments in intangible capital from 1995-2006 by 30%. Furthermore, results reveal differences in the investment patterns among the UK and Germany. In nearly all sectors investments in design and computerized information are larger in the UK. In contrast, German firms invest a higher proportion of gross output in R&D in all sectors, and advertising is also more common except for the sector trade & transport. Intangible assets have stimulated labour productivity growth in all sectors. The contribution varies between 0.17 (construction) and 0.59 (manufacturing) percentage points. In manufacturing, financial and business services innovative property capital is the most influential type of intangible capital for labour productivity, followed by economic competencies and computerized information. In all other sectors, economic competencies play the most prominent role for labour productivity growth.
urn:nbn:de:bsz:180-madoc-369381
Keywords: E22; O47; L60; L80; 330; intangible assets; economic growth; sector